Spike reproductive performance in hexaploid triticale (X Triticosecale Wittmack). Selective direct and correlated responses - Guidobaldi, H.A.=700 1 Maich, R.H.
(En)
ilus., 51-54f.
Keywords: TRITICOSECALE; FERTILIDAD; SELECCION; FERTILIDAD DE LA ESPIGUILLA; RESPUESTA CORRELACIONADAS; SELECCION DESRUPTIVA